2011
DOI: 10.1128/jvi.02424-10
|View full text |Cite
|
Sign up to set email alerts
|

The V1V2 Domain and an N-Linked Glycosylation Site in the V3 Loop of the HIV-1 Envelope Glycoprotein Modulate Neutralization Sensitivity to the Human Broadly Neutralizing Antibody 2G12

Abstract: The broadly neutralizing human monoclonal antibody 2G12 binds to a carbohydrate-dependent epitope involving three major potential N-linked glycosylation sites (PNGS) of gp120 (N295, N332, and N392). Through analysis of the sensitivity to 2G12 of pseudotyped viruses carrying envelope proteins from HIV-1 clade B-infected long-term nonprogressors, we selected two naturally occurring env clones with opposite sensitivities to 2G12, albeit harboring the 3 particular PNGS known to be essential for 2G12 binding (N295,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
4
18
0
Order By: Relevance
“…Neutralization of the BG505 pseudovirus by PGT126, which is closely related to PGT128, is surprising since structural studies of cocrystals formed with PGT128 FAb and an outer domain construct containing a mini-V3 loop (eODmV3) indicate that there is binding to a glycan determinant at position N332 (24) which is absent in BG505. Binding and neutralization of BG505 by PGT126 may be explained by promiscuity of some antibodies (25) or regulation of access to the V3 loop by V1V2 (63). In the current study, we found (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Neutralization of the BG505 pseudovirus by PGT126, which is closely related to PGT128, is surprising since structural studies of cocrystals formed with PGT128 FAb and an outer domain construct containing a mini-V3 loop (eODmV3) indicate that there is binding to a glycan determinant at position N332 (24) which is absent in BG505. Binding and neutralization of BG505 by PGT126 may be explained by promiscuity of some antibodies (25) or regulation of access to the V3 loop by V1V2 (63). In the current study, we found (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have shown that sequence variation in variable regions 1 and 2 (V1V2) can dramatically impact antibody binding and neutralization (68)(69)(70)(71)(72). Most recently, analyses in RV144 revealed that the level of binding of IgG antibodies to V1V2 correlated inversely with the rate of HIV-1 infection (73) and that there was an increased vaccine efficacy against viruses with genetic signatures in V2 (42).…”
Section: Iii) Distance To Hiv-1 Gag and Pro Of Lai (Alvac-hiv)mentioning
confidence: 99%
“…We favor this model because it relies entirely on prior evidence. Additionally, V3 mutations alter sensitivity to 2G12 (38). Moreover, residues 295 and 332 at the V3 border are also targets for autologous NAbs in newly infected individuals (3,39), and terminal mannoses in glycans at N295, N301, and N332 plus nearby V3 amino acids in gp120 JRCSF interact with NMAbs PGT127 and PGT128 from elite neutralizers (2,4).…”
Section: G12 Inhibits Cd4 and Ccr5 Binding And Blocks A Coreceptordementioning
confidence: 99%